At short telomeres Tel1 directs early replication and phosphorylates Rif1. - Akila Sridhar; Sylwia Kedziora; Anne D Donaldson (PLoS Genetics)
The replication time of Saccharomyces cerevisiae telomeres responds to TG1-3 repeat length, with telomeres of normal length replicating late during S phase and short telomeres replicating early. Here we show that Tel1 kinase, which is recruited to short telomeres, specifies their early replication, because we find a tel1Δ mutant has short telomeres that nonetheless replicate late. Consistent with a role for Tel1 in driving early telomere replication, initiation at a replication origin close to an induced short telomere was reduced in tel1Δ cells, in an S phase blocked by hydroxyurea. The telomeric chromatin component Rif1 mediates late replication of normal telomeres and is a potential substrate of Tel1 phosphorylation, so we tested whether Tel1 directs early replication of short telomeres by inactivating Rif1. A strain lacking both Rif1 and Tel1 behaves like a rif1Δ mutant by replicating its telomeres early, implying that Tel1 can counteract the delaying effect of Rif1 to control telomere replication time. Proteomic analyses reveals that in yku70Δ cells that have short telomeres, Rif1 is phosphorylated at Tel1 consensus sequences (S/TQ sites), with phosphorylation of Serine-1308 being completely dependent on Tel1. Replication timing analysis of a strain mutated at these phosphorylation sites, however, suggested that Tel1-mediated phosphorylation of Rif1 is not the sole mechanism of replication timing control at telomeres. Overall, our results reveal two new functions of Tel1 at shortened telomeres: phosphorylation of Rif1, and specification of early replication by counteracting the Rif1-mediated delay in initiation at nearby replication origins.